Description of male Risiocnemis moroensis Hamalanen 1991(Odonata: Platycnemididae) from Davao City, Mindanao Island, Philippines - Dejadena Medina, Milton Norman; Anzano Cabras, Analyn; Villanueva, Reagan Joseph Torayno (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Description of the male Risiocnemismoroensis (Hamalanen, 1991) is provided with confirmation of the taxon into appendiculata group is presented